Actitud investigativa y autovaloración sobre indagación científica en estudiantes del quinto ciclo de primaria de la Institución Educativa N° 60010 Valentin Paniagua Corazao, Belén 2025 - Vasquez Hidalgo, Gilma Cinthia (2025)
Relating the investigative attitude and self-assessment in scientific inquiry in students of the fifth cycle of primary school at Educational Institution No. 60010 Valentín Paniagua Corazao Belén 2025 was the main objective of the research. The sample studied consisted of 106 students, who were the subject of surveys and questionnaires. The methodology applied was non-experimental, field, transversal, bivariate and relational. The results show a significant relationship between the investigative attitude and self-assessment in scientific inquiry (p = .001; p < .05). However, the observed correlation is positive but low (rho = .324), which suggests that, although a favorable investigative attitude contributes to a better self assessment in scientific inquiry, its impact is limited. These findings highlight the need for complementary pedagogical strategies to strengthen self-assessment in the scientific inquiry process in students of the fifth cycle of primary school at the educational institution.